2021
DOI: 10.1159/000514439
|View full text |Cite
|
Sign up to set email alerts
|

High BMI, Aggressive Tumours and Long Console Time Are Independent Predictive Factors for Symptomatic Lymphocele Formation after Robot-Assisted Radical Prostatectomy and Pelvic Lymph Node Dissection

Abstract: <b><i>Introduction:</i></b> Lymphocele (LC) formation is a common complication which may cause severe symptoms after robot-assisted radical prostatovesiculectomy (RARP) with concomitant pelvic lymph node dissection (PLND). Compared to open radical prostatectomy, the amount of data on potential risk factors for LC formation is still limited. The aim of the present study was to identify risk factors for symptomatic LC formation (sLC) after RARP with PLND. <b><i>Methods:</i&… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
1
15
2
Order By: Relevance
“…The mean initial lymphocele size was 616 (range, 76–3295) mL. The mean drainage duration after sclerotherapy was 7.1 (Karcaaltincaba & Akhan, 2005a ; vanSonnenberg et al, 1986 ; Goßler et al, 2021 ; Heers et al, 2015 ; Zikan et al, 2015 ; Dodd et al, 1970 ; Ten Hove et al, 2021 ; Jensen et al, 1986 ; Karcaaltincaba & Akhan, 2005b ; Addo et al, 2018 ; Baek et al, 2016 ; Gill et al, 1995 ; Alago et al, 2013 ; Akhan et al, 2007 ; Chin et al, 2007 ; Filippiadis et al, 2017 ; Sacks et al, 2003 ; Kasahara et al, 2006 ; Ono et al, 2010 ; Takeda et al, 2006 ) days. Pearson’s correlation coefficient showed moderately negative correlation ( r = − 0.414) between the initial lymphocele size and drainage duration after sclerotherapy, but the association was not statistically significant ( p = 0.113) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean initial lymphocele size was 616 (range, 76–3295) mL. The mean drainage duration after sclerotherapy was 7.1 (Karcaaltincaba & Akhan, 2005a ; vanSonnenberg et al, 1986 ; Goßler et al, 2021 ; Heers et al, 2015 ; Zikan et al, 2015 ; Dodd et al, 1970 ; Ten Hove et al, 2021 ; Jensen et al, 1986 ; Karcaaltincaba & Akhan, 2005b ; Addo et al, 2018 ; Baek et al, 2016 ; Gill et al, 1995 ; Alago et al, 2013 ; Akhan et al, 2007 ; Chin et al, 2007 ; Filippiadis et al, 2017 ; Sacks et al, 2003 ; Kasahara et al, 2006 ; Ono et al, 2010 ; Takeda et al, 2006 ) days. Pearson’s correlation coefficient showed moderately negative correlation ( r = − 0.414) between the initial lymphocele size and drainage duration after sclerotherapy, but the association was not statistically significant ( p = 0.113) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lymphoceles can cause hydronephrosis, infection, abdominal pain, leg edema, and deep venous thrombosis (Karcaaltincaba & Akhan, 2005a ; vanSonnenberg et al, 1986 ). The incidence rate of symptomatic lymphoceles ranges from 2% to 9%, depending on the type of surgery (Goßler et al, 2021 ; Heers et al, 2015 ; Zikan et al, 2015 ). Asymptomatic lymphoceles resolve spontaneously without treatment (Dodd et al, 1970 ); however, symptomatic lymphoceles might require treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, some research reported perioperative adverse events associated with ePLND such as longer operation time, higher blood loss, longer hospital stays, and lymphocele. [4][5][6] Recent metaanalysis showed the incidence of perioperative complications in ePLND was significantly higher than in limited PLND (14.4% vs. 10.8%), with risk ratio of 1.61. 7 Also, previous report from Japan showed that ePLND is associated with significantly higher rate of grade 3-4 complications compared with limited PLND (4.4% vs. 1.7%).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the controversial therapeutic effect of ePLND, the importance of diagnosing cancer stage to accurately identify pelvic lymph node invasion and consider further consecutive treatment options after surgery is considered in treatment guidelines 1–3 . However, some research reported perioperative adverse events associated with ePLND such as longer operation time, higher blood loss, longer hospital stays, and lymphocele 4–6 . Recent meta‐analysis showed the incidence of perioperative complications in ePLND was significantly higher than in limited PLND (14.4% vs. 10.8%), with risk ratio of 1.61 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Lymphoceles can cause hydronephrosis, infection, abdominal pain, leg edema, and deep venous thrombosis (1,2). The incidence rate of symptomatic lymphoceles ranges from 2-9%, depending on the type of surgery (3)(4)(5). Asymptomatic lymphoceles resolve spontaneously without treatment (6); however, symptomatic lymphoceles require treatment.…”
Section: Introductionmentioning
confidence: 99%